Anodic Dissolution of lead in Acid Solution - Misbah, A.A.; El Hady, Z.A.; Khalifa, O.R. (Asian Journal of Chemistry, 2010)
Galvanostatic polarisation measurements were carried out in order to elucidate the anodic dissolution of lead in solutions of HCl, H2SO4 and HNO3. The polarisation curves exhibited similar shapes and characteristics indicating that the nature of the anion has a great influence on the anodic reaction. It was therefore concluded that the anion is directly involved in the anodic dissolution which proceeds in two steps: the first is the formation of a charged complex and the second is the dissociation of the complex and the regeneration of the anion. This is for the acids which did not form insoluble salts. Also, the anodic polarisation of lead was measured in acid-salt mixtures in which the anion concentration was kept constant (1 molar) The polarisation curves more or less coincide with each other.